2008
DOI: 10.1359/jbmr.071031
|View full text |Cite
|
Sign up to set email alerts
|

Risedronate Reduces Osteoclast Precursors and Cytokine Production in Postmenopausal Osteoporotic Women

Abstract: This paper studies the effect of oral risedronate on osteoclast precursors, osteoclast formation, and cytokine production in 25 osteoporotic women. Risedronate is effective in reducing the number of osteoclast precursors, their formation, vitality, and activity and the level of RANKL and TNF-␣ in cultures.Introduction: Bisphosphonates inhibit bone resorption by acting against osteoclasts. Some in vitro studies suggest that they induce osteoclast apoptosis; others suggest that they exert an effect on the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 46 publications
6
47
1
Order By: Relevance
“…In postmenopausal osteoporotic women only the osteoclast precursors expressing avb3 were increased, whereas the percentage of cells expressing CD14 and CD11b was not altered compared to healthy controls [17]. Also, after bisphosphonate therapy the percentage of avb3-positive precursors dropped [16].…”
Section: Osteoclast Precursor Cells In Bone-lytic Diseasesmentioning
confidence: 84%
See 1 more Smart Citation
“…In postmenopausal osteoporotic women only the osteoclast precursors expressing avb3 were increased, whereas the percentage of cells expressing CD14 and CD11b was not altered compared to healthy controls [17]. Also, after bisphosphonate therapy the percentage of avb3-positive precursors dropped [16].…”
Section: Osteoclast Precursor Cells In Bone-lytic Diseasesmentioning
confidence: 84%
“…Since the pioneering study of Ritchlin et al [7], osteoclast formation from PBMCs from rheumatic diseases [7][8][9][10][11][12][13], osteoporosis [14][15][16][17][18], periodontitis [19,20], chronic liver disease with osteopenia [21] and osteolytic cancers [22][23][24][25] was investigated. Typically, osteoclast formation of PBMCs from these patients was compared with healthy controls, either unstimulated (in the absence of macrophage colony forming factor (M-CSF) and RANKL) or stimulated (in the presence of M-CSF and RANKL).…”
Section: Osteoclast Formation From Pbmcs From Patients With Bone-lytimentioning
confidence: 99%
“…Circulating CD14+ cells are increased in those with osteoporosis compared with healthy controls [44]. In a 3-month study, the bisphosphonate risedronate reduced levels of circulating CD14+ cells in women with osteoporosis [45]. The current study adds to our understanding of sCD14 biology in a population of older, community-dwelling adults.…”
Section: Discussionmentioning
confidence: 67%
“…5), in agreement with prior reports of bisphosphonate inhibitory effects on monocyte TNF, IL-1, and IL-6 expression in vitro [24][25][26][27][28][29] and on TNF, IL-1, and IL-6 levels in osteoporotic patients. [30][31][32] Previously we demonstrated that epidermal keratinocytes are the primary cellular source for the expression of cutaneous inflammatory mediators in fracture rats and mice and in CRPS patient skin. 20,[52][53][54] Interestingly, TNF and IL-6 levels are also increased in the skin and experimental skin blister fluid of CRPS affected limbs.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Bisphosphonate treatment also reduces serum levels of TNF, IL-1, and IL-6 in osteoporosis patients. [30][31][32] Because bisphosphonates can potentially reverse pain, osteoclast activation, bone loss, inflammation, and antigen presentation, they present an attractive therapeutic approach in CRPS. The aim of the current study was to determine whether bisphosphonate treatments could inhibit the post-fracture development of nociceptive sensitization, reverse established pain behaviors, preserve trabecular bone integrity, and prevent the expression of cutaneous inflammatory mediators and immunocomplex deposition in skin and nerve after fracture.…”
Section: Introductionmentioning
confidence: 99%